Examples from the Initiatives of Cyprus Orthodox Clergymen Related to Enosis with Documents from the Venizelos Archive (1914-1954) - Nilüfer Erdem (Yakın Dönem Türkiye Araştırmaları)
Our article aims to present examples of the Enosis, that is the attempts of the Orthodox clergymen to unite Cyprus with Greece in 1914–1954 and to highlight their leadership role in the Greek community. The period we consider starts with the announcement that Britain had annexed the island unilaterally and extends until the Cyprus problem was moved to the United Nations. Consistent with our aims, the documents relating to Cyprus held in the Digital Venizelos Archive (hereafter named the Venizelos Archive) were predominantly used. Although theGreeks considered that the island’s transition to the administration of Britain would enable them to reach their ultimate goals more easily, they did not hesitate to complain about the British administration on various occasions. The actors on the island changed during the period; however, no changes were noticed in the discourse or actions.